Analyzing Environmental Dynamics in the Center of Iran: Impacts of Climatic and Environmental Factors Using Remote Sensing and Spatial Analysis in Google Earth Engine and R Software - Mohamad Ali Ghoveh Nodoushan; Ali Akbar Jamali; Seyed Masood Monavari; Seyed Abolghasem Mirhoseini; Mehdi Dehghani Zahedani (Journal of Environmental Health and Sustainable Development)
Introduction: Environmental changes driven by anthropogenic and natural factors significantly affect human health, the environment, and economic systems globally. This study investigated the ecological impacts of environmental variables in the Yazd-Ardakan Plain using remote sensing data and geospatial analysis. Materials and Methods: Google Earth Engine (GEE) and R software were used to assess spatiotemporal trends from 2018 to 2023 using data from Landsat-8, Sentinel-2, and Sentinel-5P. Key indices, including the Normalized Difference Vegetation Index (NDVI), temperature, surface runoff, and concentrations of NO2, CO, O3, and SO2, were calculated to evaluate patterns in green space, air quality, temperature, and precipitation. Results: Elevated NO2 and CO levels were observed in the centers of Yazd and  Ardakan, with O3 and SO2 peaking in 2019-2020 and improving by 2023. The highest aerosol concentrations were in 2019 and 2023, with a decrease in 2022. NDVI values peaked in 2020 but declined until 2023. The spatial analysis identified denser green spaces in Ardakan, elevated temperatures in Steel, and consistent precipitation across the regions. A positive correlation was found between temperature and pollution, whereas NDVI and precipitation showed negative correlations with temperature, indicating that vegetation loss exacerbates the effects of warming and pollution. Conclusion: This study highlights significant climatic and environmental changes in the Yazd-Ardakan plain from 2018 to 2023, including rising temperatures and pollution, alongside declining precipitation and vegetation. These trends underscore the need for targeted management strategies to mitigate environmental degradation, protect public health, and promote sustainable development through advanced monitoring and policy intervention.